INVESTIGATING THE ARGUMENTS OF NECESSARY OF EXISTENCE (WĀJIB AL-WUJŪD) IN SUHRAWARDĪ’S PHILOSOPHY BASED ON AL-TALWĪḤĀT AND ḤIKMAH AL-ISHRĀQ - Mohamad Mahdi Davar (Sekolah Tinggi Agama Islam Sadra, 2024)
Suhrawardī has presented arguments to support the existence of wājib al-wujūd in many of his works. One of the most fundamental of these arguments, which also has a forward-looking feature, is the one he presents in his books al-Talwīḥāt and Ḥikmah al-Ishrāq. To prove the existence of God, Suhrawardī devised three arguments in al-Talwīḥāt and one argument in Ḥikmah al-Ishrāq, all of which are interpretations of the ṣiddīqīn argument. In this article four of Suhrawardī’s arguments, three of them in al-Talwīḥāt and one of them in Ḥikmah al-Ishrāq are reviewed. the main aim of this study is to analyze and explain Suhrawardī’s arguments, due to their importance in philosophy and theology, with the descriptive-analytical method and using library-based collecting data. The arguments presented in the al-Talwīḥāt are succinct, and what made these claims essential was the evaluation of their robustness and content. The significance of his first and third arguments in this book is that they do not require the denial of the vicious circle as a precondition, and by assuming the likelihood of both the vicious circle and infinite regress, the necessity of existence is demonstrated. On the other hand, his argument in Ḥikmah al-Ishrāq, which, like his second argument, is based on the refutation of the vicious circle and infinite regress, includes innovative features and should be investigated thoroughly.